Ubiqüitat de la ironia –o, si més no, alguns dels seus usos entre els poetes actuals - Ballart, Pierre (Caplletra. Revista Internacional de Filologia, 2006)
The incidence of irony in the genre of lyric poetry has caused some special effects, mainly after modernity turned this disposition of thought into an irreplaceable element when, thanks to the contribution of the Romantic poet Friedrich Schlegel, complicities between poets and readers were stipulated. The present article tries to evaluate the validity of these presuppositions by studying the use of ironic procedures in the poetic texts of a number of authors of great importance now. The relevance of the authors analyzed is justified not only by the poets’ relation to an absolute diversity of styles and programs, but also, by the fact that it is able to represent all the literary generations that are currently producing Catalan poetry. The paper, therefore, aims at characterizing the features of poetic irony, and also, by virtue of its synchronic division, at giving accounts of up to what extent the resource is adapted to the expressive necessities of Catalan poetry at the present moment.